Wavelength conversion member

JP2025036060APending Publication Date: 2025-03-14NIPPON ELECTRIC GLASS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024069882
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-29
Filing Date
2024-04-23
Publication Date
2025-03-14

Smart Images

  • Figure 2025036060000001_ABST
    Figure 2025036060000001_ABST
Patent Text Reader

Abstract

To provide a wavelength conversion member capable of easily adjusting chromaticity when irradiated with light from an LED or LD.SOLUTION: A wavelength conversion member 1 is provided, comprising a wavelength conversion member body 10 consisting of an inorganic phosphor 12 dispersed in an organic matrix 11, and a filter layer 20 formed on one surface of the wavelength conversion member body 10, the filter layer 20 being configured to suppress transmission of light in an excitation band of the inorganic phosphor 12 and allow transmission of light of an emission peak wavelength of the inorganic phosphor 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a wavelength conversion member for converting the wavelength of light emitted by a light emitting element such as a light emitting diode (LED) or a laser diode (LD) into another wavelength. [Background technology]

[0002] In recent years, light sources using LEDs and LDs have been attracting increasing attention as next-generation light sources to replace fluorescent lamps and incandescent lamps, due to their low power consumption, small size, light weight, and easy light intensity adjustment. Patent Document 1, for example, discloses an example of such a next-generation light source, in which a wavelength conversion member is disposed on an LED that emits blue light, and the wavelength conversion member absorbs part of the light from the LED and converts it to yellow light. This light source emits white light, which is a composite light of the blue light emitted from the LED and the yellow light emitted from the wavelength conversion member.

[0003] Conventionally, wavelength conversion materials have been made by dispersing inorganic phosphors in a resin matrix. However, when such wavelength conversion materials are used, there is a problem that the resin is easily degraded by the light from the LED, which reduces the brightness of the light source. In particular, there is a problem that the resin matrix is ​​degraded by the heat and high-energy short-wavelength (blue to ultraviolet) light emitted by the LED, causing discoloration and deformation.

[0004] Therefore, wavelength conversion members made of completely inorganic solids in which inorganic phosphors are dispersed and fixed in a glass matrix instead of a resin have been proposed (see, for example, Patent Documents 2 and 3). These wavelength conversion members have the advantage that the glass base material is less likely to deteriorate due to heat or irradiated light from the LED chip, and are less likely to suffer from problems such as discoloration or deformation. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2000-208815 [Patent Document 2] Japanese Patent Application Laid-Open No. 2003-258308 [Patent Document 3] Patent No. 4895541 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the light obtained by a light-emitting device using a wavelength conversion material is a composite light that combines the excitation light emitted from the LED and passed through the wavelength conversion material, as described above, and the fluorescence emitted from the phosphor, making it difficult to effectively utilize the color of the fluorescence and sometimes making it difficult to obtain light of the desired chromaticity.

[0007] In view of the above, an object of the present invention is to provide a wavelength conversion member that can emit light of a desired chromaticity when irradiated with light from an LED or LD. [Means for solving the problem]

[0008] A wavelength conversion member that solves the above problems will be described.

[0009] A wavelength conversion member according to aspect 1 of the present invention is a wavelength conversion member comprising a wavelength conversion member body formed by dispersing an inorganic phosphor in an inorganic matrix, and a filter layer provided on one surface of the wavelength conversion member body, wherein the filter layer suppresses transmission of light in the excitation band of the inorganic phosphor and transmits light of the emission peak wavelength of the inorganic phosphor.

[0010] A wavelength conversion member according to aspect 2 of the present invention is preferably, in aspect 1, such that the excitation band of the inorganic phosphor is between 300 nm and 480 nm, and the emission peak wavelength of the inorganic phosphor is 500 nm or more and 700 nm or less.

[0011] A wavelength conversion member according to aspect 3 of the present invention is the same as that of aspect 1 or 2, wherein the filter layer is preferably a dielectric multilayer film.

[0012] A wavelength conversion member according to a fourth aspect of the present invention is preferably in accordance with the third aspect, wherein the total number of laminated dielectric multilayer films is 10 or more.

[0013] In the wavelength conversion member according to aspect 5 of the present invention, in any one of aspects 1 to 4, it is preferable that the inorganic phosphor includes at least one selected from a nitride phosphor and an oxynitride phosphor.

[0014] A wavelength conversion member according to a sixth aspect of the present invention is the same as any one of the first to fifth aspects, wherein the inorganic matrix preferably contains glass or ceramics.

[0015] In the wavelength conversion member according to aspect 7 of the present invention, in any one of aspects 1 to 6, the wavelength conversion member is placed under a light source with an excitation peak wavelength of 450 nm, and the chromaticity calculated from the energy distribution spectrum of light measured by taking light emitted from the lower surface of the wavelength conversion member into an integrating sphere is preferably a chromaticity Cx of 0.45 to 0.65 and a chromaticity Cy of 0.35 to 0.50.

[0016] A wavelength conversion member according to aspect 8 of the present invention is the same as any one of aspects 1 to 7, wherein the cut-on wavelength of the filter layer is preferably 480 nm or more and 680 nm or less.

[0017] A wavelength conversion member according to a ninth aspect of the present invention is preferably the same as any one of the first to eighth aspects, in which the filter layer is disposed on the emission surface side of the wavelength conversion member.

[0018] A wavelength conversion member according to a tenth aspect of the present invention is preferably in accordance with aspect 9, wherein the filter layer also serves as a filter that cuts off part of the emission spectrum of the inorganic phosphor on the short wavelength side.

[0019] A wavelength conversion member according to aspect 11 of the present invention is a wavelength conversion member comprising an inorganic phosphor dispersed in an inorganic matrix, characterized in that the inorganic phosphor comprises at least one selected from the group consisting of oxide phosphors, nitride phosphors, oxynitride phosphors, chloride phosphors, oxychloride phosphors, halide phosphors, aluminate phosphors and halophosphate chloride phosphors, and the content of the inorganic phosphor is 25 mass% or more. [Effects of the Invention]

[0020] According to the present invention, it is possible to provide a wavelength conversion member that can emit light of a desired chromaticity when irradiated with light from an LED or LD. [Brief explanation of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a wavelength conversion member according to a first embodiment of the present invention. [Figure 2] 1 is a schematic side view of a light-emitting device according to one embodiment of the present invention; [Figure 3] FIG. 1 is a schematic cross-sectional view of a filter layer according to a first embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view of a wavelength conversion member according to a second embodiment of the present invention. [Figure 5] 3 is a graph showing a spectral transmittance curve at an incident angle of 0° of the filter layer according to the first embodiment of the present invention. [Figure 6] 1 is a graph showing the emission spectra of Example 1 and Comparative Example 1. [Figure 7] 1 is a graph showing the emission spectra of Examples 2 to 6 (a) and Comparative Examples 2 and 3 (b). [Figure 8] 1 is a graph showing the emission spectra of Examples 7 and 8. [Figure 9] 1 is a diagram showing chromaticity Cx and chromaticity Cy of Examples 1 to 8 and Comparative Examples 1 to 3. FIG. [Figure 10] 1 is a graph showing spectral transmittance curves at an incident angle of 0° for the filter layers obtained in Examples 9 to 11. [Figure 11]1 is a graph showing the emission spectra of Examples 9 to 11. DETAILED DESCRIPTION OF THE INVENTION

[0022] (First embodiment) Fig. 1 is a schematic cross-sectional view showing a wavelength conversion member 1 according to a first embodiment of the present invention. As shown in Fig. 1, the wavelength conversion member 1 is constructed by providing a filter layer 20 on one surface of a wavelength conversion member body 10. In this embodiment, the wavelength conversion member body 10 is formed by dispersing inorganic phosphors 12 in an inorganic matrix 11. In this embodiment, the filter layer 20 is formed on one surface of the wavelength conversion member body 10.

[0023] (filter layer 20) The wavelength conversion member 1 of the first embodiment of the present invention includes a filter layer 20 on one surface of the wavelength conversion member body 10. The filter layer 20 is a filter layer that suppresses transmission of light with a wavelength in the excitation band of the inorganic phosphor 12 and transmits light with a wavelength of the emission peak of the inorganic phosphor 12.

[0024] FIG. 2 shows an example of an embodiment of a light-emitting device of the present invention. As shown in FIG. 2, the light-emitting device 3 includes a wavelength conversion member 1 and a light source 30. The light source 30 irradiates the wavelength conversion member 1 with excitation light L0 having a wavelength in the excitation band of the inorganic phosphor 12 contained in the wavelength conversion member 1. The excitation light L0 incident on the wavelength conversion member 1 is converted into light of a different wavelength upon entering the inorganic phosphor 12 contained in the wavelength conversion member 1, and is emitted as fluorescence L1 having the emission peak wavelength of the inorganic phosphor 12 from the wavelength conversion member 1 opposite the light source 30. In addition, in the light-emitting device 3 shown in FIG. 2, the filter layer 20 is typically formed on the emission surface side of the wavelength conversion member 1 (the right side in FIG. 2), which is the opposite side of the wavelength conversion member 1 from the light source 30. The wavelength conversion member 1 and the light-emitting device 3 are manufactured by forming the filter layer 20 on the surface of the emission surface side of the wavelength conversion member main body 10. As a result, in the first embodiment of the present invention, the filter layer 20 suppresses transmission of the excitation light L0 that would otherwise be transmitted without being wavelength-converted and transmits the fluorescence L1. As a result, it is possible to effectively utilize the fluorescence of the inorganic phosphor 12 and easily obtain light of a desired chromaticity in the light-emitting device 3. Note that, by changing the configuration of the filter layer 20 as necessary, it is possible to transmit a portion of the excitation light L0 and emit it as light combined with the fluorescence L1.

[0025] Here, the excitation band of inorganic phosphor 12 is preferably between 300 nm and 480 nm, more preferably between 380 nm and 470 nm, and even more preferably between 430 nm and 460 nm. Furthermore, the wavelength of the emission peak of inorganic phosphor 12 is preferably between 500 nm and 700 nm, more preferably between 550 nm and 670 nm, and even more preferably between 580 nm and 650 nm. This further reduces the transmission of blue light, which is excitation light, and allows for greater transmission of yellow to red light, which is fluorescence from inorganic phosphor 12, making it easier to obtain light of the desired chromaticity in light-emitting device 3.

[0026] The filter layer 20 may be a single layer or a multilayer (dielectric multilayer) made of an oxide, nitride, fluoride, etc. The filter layer 20 does not need to be formed on the entire one surface of the wavelength conversion member body 10, but may be formed on at least a part of the surface of the wavelength conversion member body 10.

[0027] Such a filter layer 20 can be formed, for example, by a dielectric multilayer film 40 having incident angle dependency, which is formed by alternately stacking low-refractive-index layers 41L having a relatively low refractive index and high-refractive-index layers 41H having a relatively high refractive index, as shown in Fig. 3. The low-refractive-index layers 41L can be formed, for example, of silicon oxide, aluminum oxide, magnesium fluoride, etc. The high-refractive-index layers 41H can be formed, for example, of niobium oxide, titanium oxide, zirconium oxide, lanthanum oxide, tantalum oxide, yttrium oxide, gadolinium oxide, tungsten oxide, hafnium oxide, silicon oxynitride, silicon nitride, aluminum nitride, etc.

[0028] The thickness of the low refractive index layer 41L of the dielectric multilayer film 40 can be, for example, about 1.5 nm to 150 nm. The thickness of the high refractive index layer 41H can be, for example, about 1.5 nm to 150 nm. The thickness of each layer in the dielectric multilayer film 40 is not limited to the above.

[0029] The total number of high-refractive-index layers 41H and low-refractive-index layers 41L in the dielectric multilayer film 40 is preferably 10 or more, more preferably 14 or more, even more preferably 16 or more, even more preferably 18 or more, even more preferably 20 or more, even more preferably 22 or more, even more preferably 24 or more, even more preferably 25 or more, and preferably 200 or less, more preferably 150 or less, even more preferably 100 or less, even more preferably 80 or less, and even more preferably 60 or less. If the total number of layers is too small, it may be difficult to narrow the wavelength band in the transition portion from the transmission wavelength range to the non-transmission wavelength range in the dielectric multilayer film 40 and achieve a steep gradient. On the other hand, if the total number of layers is too large, distortion occurs in the dielectric multilayer film 40, making it more susceptible to peeling or cracking from the substrate.

[0030] The total thickness of the dielectric multilayer film 40 is preferably 15 nm or more, more preferably 50 nm or more, even more preferably 100 nm or more, even more preferably 300 nm or more, even more preferably 500 nm or more, even more preferably 700 nm or more, even more preferably 1000 nm or more, and preferably 3000 nm or less, more preferably 2500 nm or less. If the total thickness is too small, it may be difficult to narrow the wavelength band in the transition portion from the transmission wavelength range to the non-transmission wavelength range in the dielectric multilayer film 40 and achieve a steep gradient. On the other hand, if the total thickness is too large, distortion occurs in the dielectric multilayer film 40, making it more susceptible to peeling from the substrate or cracking.

[0031] The dielectric multilayer film 40 can be formed on the surface of the wavelength conversion member body 10 using a known film formation method such as a sputtering method, a vacuum deposition method, an ion beam method, an ion plating method, a CVD method, etc. Among these film formation methods, the sputtering method is preferred because it allows the thickness of each layer to be controlled with high precision and can provide a dielectric multilayer film 40 with stable film quality.

[0032] The cut-on wavelength of the filter layer 20 is preferably 480 nm or more, more preferably 510 nm or more, even more preferably 530 nm or more, even more preferably 550 nm or more, even more preferably 560 nm or more, even more preferably 570 nm or more, even more preferably 575 nm or more, and preferably 680 nm or less, more preferably 660 nm or less, even more preferably 640 nm or less, even more preferably 620 nm or less, and even more preferably 600 nm or less. When the cut-on wavelength of the filter layer 20 is equal to or greater than the above-mentioned lower limit, the transmission of light with wavelengths in the excitation band of the inorganic phosphor 12 can be further suppressed, and in particular, the transmission of light with wavelengths in the excitation band incident at wide angles can be more reliably suppressed. The cut-on wavelength of the filter layer 20 can be appropriately selected depending on the type of inorganic phosphor 12 used in the wavelength conversion member body 10, but is preferably equal to or less than the emission peak wavelength of the inorganic phosphor 12, and more preferably shorter than the emission peak wavelength of the inorganic phosphor 12. However, when the cut-on wavelength of the filter layer 20 is equal to or less than the upper limit, yellow to red light, which is the fluorescence of the inorganic phosphor 12, can be more easily transmitted, making it easier to obtain light of the desired chromaticity in the light-emitting device 3.

[0033] The cut-on wavelength of the filter layer 20 can be determined by measuring the spectral transmittance curve at an incident angle of 0° for a sample in which the filter layer 20 is formed on a glass substrate with a thickness of 0.5 mm. In the spectral transmittance curve, the wavelength at which the transmittance drops to 50% in the direction from the long wavelength side to the short wavelength side can be defined as the cut-on wavelength.

[0034] When the filter layer 20 is the above-described dielectric multilayer film 40, the cut-on wavelength of the filter layer 20 can be shifted to the long wavelength side, for example, by increasing the overall thickness of the low refractive index layer 41L and the high refractive index layer 41H without changing the ratio of their thicknesses. In addition to the above, by adjusting the balance between the thicknesses of the low refractive index layer 41L and the high refractive index layer 41H in the filter layer 20, the transmission of light in a specific wavelength range can be adjusted.

[0035] The filter layer 20 may also serve as a filter that cuts off a portion of the short wavelength side of the emission spectrum of the inorganic phosphor 12. When the filter layer 20 is provided as in the present embodiment, the chromaticity of the light-emitting device 3 is likely to yellow-shift. However, when the filter layer 20 also serves as a filter that cuts off a portion of the short wavelength side of the emission spectrum of the inorganic phosphor 12 as described above, the yellow-shift can be suppressed in the light-emitting device 3, and the chromaticity can be made more reddish.

[0036] In order to suppress yellow shift in the light-emitting device 3 and achieve a redder chromaticity, the cut-on wavelength of the filter layer 20 is preferably 550 nm or more, even more preferably 560 nm or more, even more preferably 570 nm or more, even more preferably 575 nm or more, and is preferably 680 nm or less, more preferably 660 nm or less, even more preferably 640 nm or less, even more preferably 620 nm or less.

[0037] In the light-emitting device 3, the yellow shift can be suppressed and a redder chromaticity can be achieved by increasing the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10. However, increasing the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10 may reduce the luminous flux value of the light-emitting device 3. In contrast, by designing the cut-on wavelength of the filter layer 20 to be on the long wavelength side as described above, the yellow shift can be suppressed in the light-emitting device 3 and a redder chromaticity can be achieved. Therefore, the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10 can be designed to be low, thereby further increasing the luminous flux value of the light-emitting device 3.

[0038] (Wavelength conversion member body 10) The wavelength conversion material body 10 is, for example, phosphor glass containing a glass matrix and phosphor powder. The phosphor powder is dispersed in the glass matrix. The shape of the wavelength conversion material body 10 may be selected appropriately depending on the shape of the light emitting device, but in this embodiment, it is a rectangular plate.

[0039] (Inorganic Matrix 11) The inorganic matrix 11 is not particularly limited as long as it can be used as a dispersion medium for phosphor particles such as the inorganic phosphor 12. For example, when the inorganic matrix 11 is a glass matrix, borosilicate glass, phosphate glass, tin phosphate glass, bismuthate glass, tellurite glass, or the like can be used. The inorganic matrix 11 may also be a ceramic matrix instead of a glass matrix, in which case the thermal conductivity of the wavelength conversion member 1 can be further improved. Examples of ceramics that constitute the ceramic matrix include Al2O3, MgO, and AlN. The inorganic matrix 11 may also be a glass ceramic, or an inorganic matrix other than glass or ceramic.

[0040] The glass matrix is ​​preferably glass with a low content of alkali metal components in the glass matrix. This suppresses the formation of color centers in the glass matrix, which act as absorption sources for excitation light and fluorescence, and can suppress a decrease in the luminescence intensity of the wavelength conversion member 1. It can also suppress deterioration of the glass matrix over time under high temperature and high humidity conditions. The glass composition of the glass matrix is ​​preferably, in mole percent, Li2O+Na2O+K2O at 0% to 10%, more preferably Li2O+Na2O+K2O at 0% to 5%, and even more preferably Li2O+Na2O+K2O at 0% to 3%.

[0041] For example, borosilicate glasses may contain, in mole percent, 10% to 85% SiO2, 0.1% to 50% B2O3, 0% to 25% Al2O3, 0% to 10% Li2O + Na2O + K2O, and 0% to 50% MgO + CaO + SrO + BaO. Furthermore, tin phosphate glasses may contain, in mole percent, 30% to 90% SnO and 51% to 70% P2O. Examples of tellurite glasses may contain, in mole percent, 50% or more TeO2, 0% to 45% ZnO, 0% to 50% RO (where R is at least one selected from Ca, Sr, and Ba), and 30% to 50% La2O3 + Gd2O3 + YO.

[0042] In particular, the borosilicate glass preferably contains, in mole percent, 30% to 85% SiO2, 4.3% to 20% B2O3, 30% to 25% Al2O, 0% to 3% Li2O, 0% to 3% Na2O, 0% to 3% K2O, 0% to 3% Li2O+Na2O+K2O, 0% to 35% MgO, 0% to 35% CaO, 0% to 35% SrO, 0% to 35% BaO, 0.1% to 45% MgO+CaO+SrO+BaO, and 0% to 5% ZnO.

[0043] From the viewpoint of further lowering the softening point of the glass matrix, examples of borosilicate glasses that contain, in mole percent, 30% to 80% SiO2, 1% to 40% B2O3, 0.1% to 35% Li2O+Na2O+K2O, 0.1% to 45% MgO+CaO+SrO+BaO, and 0.001% to 10% CeO2+As2O3+MoO2+WO3, and glasses that contain 30% to 80% SiO2, 1% to 55% B2O3, 0% to 20% Li2O, 0% to 25% Na2O, 0% to 25% K2O, 0.1% to 35% Li2O+Na2O+K2O, and 0.001% to 10% CeO2+As2O3+MoO2+WO3 can also be mentioned.

[0044] The reasons for limiting the glass composition range in this way will be explained below. In the following explanation, "%" means "mol %" unless otherwise specified.

[0045] SiO2 is a component that forms a glass network. The SiO2 content is preferably 30% to 85%, and more preferably 35% to 80%. If the SiO2 content is too low, weather resistance and mechanical strength tend to decrease. On the other hand, if the SiO2 content is too high, the sintering temperature becomes high, making the inorganic phosphor more susceptible to deterioration during the production of the wavelength conversion member 1.

[0046] B2O3 is a component that lowers the melting temperature and significantly improves meltability. The B2O3 content is preferably 4.3% to 20%, and more preferably 4.3% to 18%. If the B2O3 content is too low, the fluidity of the glass will be poor in the firing step during production of the wavelength conversion member 1, and bubbles will likely remain in the glass matrix. On the other hand, if the B2O3 content is too high, the weather resistance will likely decrease.

[0047] Al2O3 is a component that improves weather resistance and mechanical strength. The Al2O3 content is preferably 0% to 25%, and more preferably 0.1% to 20%. If the Al2O3 content is too high, the melting property tends to decrease.

[0048] Li2O, Na2O, and K2O are components that lower the melting temperature, improving meltability, and also lower the softening point. However, if the content of these components is too high, weather resistance is likely to decrease, and the luminous intensity is likely to decrease over time due to light irradiation from an LED or LD. Therefore, the content of Li2O + Na2O + K2O is preferably 0% to 3%, more preferably 0% to 2%. Furthermore, the content of each of the Li2O, Na2O, and K2O components is preferably 0% to 3%, more preferably 0% to 2%. When Li2O, Na2O, and K2O are contained, it is preferable to use a mixture of two or more, especially three types. In this way, the mixed alkali effect can suppress the decrease in luminous intensity over time due to light irradiation from an LED or LD. From the viewpoint of further lowering the softening point of the glass matrix, the total content of Li2O, Na2O, and KO is preferably 0.1% to 35%, more preferably 1% to 25%, and even more preferably 2% to 20%. If the content of these components is too low, the softening point of the glass matrix is ​​unlikely to be lowered, whereas if the content of these components is too high, the chemical durability and weather resistance of the glass matrix are likely to be reduced.

[0049] MgO, CaO, SrO, and BaO are components that lower the melting temperature, improve meltability, and lower the softening point. As mentioned above, unlike alkali metal components, these components do not affect the decrease in luminous intensity of the wavelength conversion member 1 over time. The content of MgO+CaO+SrO+BaO is preferably 0.1% to 45%, more preferably 0.1% to 40%, 0.1% to 35%, 1% to 30%, and particularly preferably 5% to 25%. If the content of MgO+CaO+SrO+BaO is too low, the softening point is unlikely to decrease. On the other hand, if the content of MgO+CaO+SrO+BaO is too high, the weather resistance is likely to decrease. The content of each of MgO, CaO, SrO, and BaO is preferably 0% to 35%, more preferably 0.1% to 33%, and even more preferably 1% to 30%. If the content of these components is too high, the weather resistance tends to decrease.

[0050] ZnO is a component that lowers the melting temperature and improves meltability. The ZnO content is preferably 0% to 5%, more preferably 1% to 4.5%, and even more preferably 1.8% to 4%. If the ZnO content is too high, weather resistance tends to decrease. In addition, phase separation tends to occur, reducing transmittance and, as a result, reducing luminous intensity.

[0051] Various components may also be contained within a range that does not impair the effects of the present invention. For example, P2O5, La2O3, Ta2O5, TeO2, TiO2, Nb2O5, Gd2O3, Y2O3, CeO2, Sb2O3, SnO2, Bi2O3, As2O3, MoO2, WO3, and ZrO2 may each be contained in an amount of 15% or less, preferably 10% or less, and particularly 5% or less, with a total amount of 30% or less. In particular, by including 0.001% to 10% of CeO2 + As2O3 + MoO2 + WO3 in the glass composition, the decrease in luminescence intensity over time of the wavelength conversion member can be suppressed. Among these, Ce is particularly preferred because it can significantly suppress the decrease in luminescence intensity over time and, further, the glass powder itself is less likely to be colored. F can also be contained. Since F has the effect of lowering the softening point, by incorporating it in place of an alkali metal component, which is one of the causes of color center formation, it is possible to suppress a decrease in emission intensity over time while maintaining a low softening point. The content of F is preferably 0% to 10%, more preferably 0% to 8%, and particularly preferably 0.1% to 5%, in anion %.

[0052] Fe and Cr are components that reduce visible light transmittance and cause a decrease in luminous intensity. Therefore, the Fe content is preferably 1000 ppm or less, more preferably 500 ppm or less. Furthermore, the Cr content is preferably 500 ppm or less, more preferably 100 ppm or less. However, in order to prevent the inclusion of Fe and Cr in the glass, it is necessary to use expensive high-purity raw materials, which tends to increase production costs. Therefore, from the viewpoint of reducing production costs, the Fe and Cr contents are each preferably 5 ppm or more, more preferably 10 ppm or more.

[0053] The softening point of the glass matrix is ​​preferably 250°C to 1000°C, more preferably 300°C to 950°C, and even more preferably 500°C to 900°C. If the softening point of the glass matrix is ​​too low, the mechanical strength and chemical durability of the wavelength conversion member 1 may be reduced. Furthermore, since the glass matrix itself has low heat resistance, it may be softened and deformed by the heat generated by the inorganic phosphor 12. On the other hand, if the softening point of the glass matrix is ​​too high, the inorganic phosphor 12 may be deteriorated during the firing step during production, resulting in a reduction in the luminescence intensity of the wavelength conversion member 1. From the viewpoint of further improving the chemical stability and mechanical strength of the wavelength conversion member 1, the softening point of the glass matrix is ​​preferably 500°C or higher, more preferably 550°C or higher, even more preferably 600°C or higher, even more preferably 650°C or higher, even more preferably 700°C or higher, even more preferably 750°C or higher, particularly preferably 800°C or higher, and most preferably 820°C or higher. Examples of glasses constituting such glass matrices include borosilicate glasses. However, as the softening point of the glass matrix increases, the firing temperature also increases, which tends to result in higher manufacturing costs. Furthermore, if the inorganic phosphor 12 has low heat resistance, the inorganic phosphor 12 may be degraded by firing. In particular, when a nitride phosphor or oxynitride phosphor with relatively low heat resistance is used as the inorganic phosphor 12, the inorganic phosphor 12 may be thermally degraded or may react with the glass matrix, causing foaming and resulting in a significant decrease in luminescence intensity and mechanical strength.Therefore, when the wavelength conversion member 1 is to be manufactured more inexpensively or when the heat resistance of the inorganic phosphor 12 is lower, the softening point of the glass matrix is ​​preferably 900°C or less, more preferably 850°C or less, even more preferably 840°C or less, even more preferably 830°C or less, even more preferably 820°C or less, even more preferably 810°C or less, even more preferably 800°C or less, even more preferably 790°C or less, even more preferably 780°C or less, even more preferably 760°C or less, even more preferably 750°C or less, even more preferably 700°C or less, even more preferably 650°C or less, even more preferably 600°C or less, even more preferably 550°C or less, even more preferably 530°C or less, even more preferably 500°C or less, particularly preferably 480°C or less, and most preferably 460°C or less. Examples of glasses constituting such a glass matrix include borosilicate glass, tin phosphate glass, bismuthate glass, and tellurite glass.

[0054] (Inorganic Phosphor 12) The inorganic phosphor 12 is at least one selected from the group consisting of, for example, oxide phosphors (including garnet-based phosphors such as YAG phosphors), nitride phosphors, oxynitride phosphors, chloride phosphors, oxychloride phosphors, halide phosphors, aluminate phosphors, and halophosphate chloride phosphors. Of these inorganic phosphors 12, oxide phosphors, nitride phosphors, and oxynitride phosphors are preferred because they have high heat resistance and are relatively resistant to deterioration during firing.

[0055] Nitride phosphors and oxynitride phosphors are characterized by converting excitation light from near ultraviolet to blue into a wide wavelength range from green to red, and by their relatively high luminous intensity. A coated inorganic phosphor 12 may be used to prevent heat generated by the inorganic phosphor 12 from being conducted to the inorganic matrix 11. This prevents the active movement of electrons, holes, and alkali ions in the inorganic matrix 11, thereby suppressing the formation of color centers. Oxides are preferred as coating materials. While sulfide phosphors are another example of phosphors other than those mentioned above, they are preferably not used in the present invention because they tend to deteriorate over time or react with the inorganic matrix 11, resulting in a decrease in luminous intensity.

[0056] Examples of the inorganic phosphor 12 include those that have an excitation band between 300 nm and 500 nm wavelengths and an emission peak between 500 nm and 780 nm wavelengths, and in particular those that emit green (500 nm to 540 nm wavelengths), yellow (540 nm to 595 nm wavelengths), and red (600 nm to 700 nm wavelengths).

[0057] As an inorganic phosphor with an excitation band in the ultraviolet to near-ultraviolet wavelength range of 300 nm to 440 nm and a green emission peak, SrAl2O4:Eu 2+ , SrBaSiO4:Eu 2+ , Y3(Al,Gd)5O 12 :Ce 3+ , SrSiON:Eu 2+ , BaMgAl 10 O 17 :EU 2+ ,Mn 2+ , Ba2MgSi2O7:Eu 2+ , Ba2SiO4:Eu 2+ , Ba2Li2Si2O7:Eu 2+ , BaAl2O4:Eu 2+ etc.

[0058] As an inorganic phosphor that has an excitation band in the blue wavelength range of 440 nm to 480 nm and a green emission peak, SrAl2O4:Eu 2+ , Lu3Al5O 12:Ce, SrBaSiO4:Eu 2+ , Y3(Al,Gd)5O 12 :Ce 3+ , SrSiON:Eu 2+ , β-SiAlON:Eu 2+ etc.

[0059] As an inorganic phosphor having an excitation band in the ultraviolet to near-ultraviolet wavelength range of 300 nm to 440 nm and a yellow emission peak, La3Si6N 11 :Ce 3+ etc.

[0060] As an inorganic phosphor having an excitation band in the blue wavelength range of 440 nm to 480 nm and a yellow emission peak, Y3(Al,Gd)5O 12 :Ce 3+ , Lu3Al5O 12 :Ce, Sr2SiO4:Eu 2+ Examples include:

[0061] As an inorganic phosphor having an excitation band in the ultraviolet to near-ultraviolet wavelength range of 300 nm to 440 nm and a red emission peak, MgSr3Si2O8:Eu 2+ ,Mn 2+ , Ca2MgSi2O7:Eu 2+ ,Mn 2+ etc.

[0062] As an inorganic phosphor having an excitation band in the blue wavelength range of 440 nm to 480 nm and an emission peak in the yellow to red range, CaAlSiN3:Eu 2+ (CASN), (Ca,Sr)AlSiN3:Eu 2+ (SCASN), CaSiN3:Eu 2+ , (Ca,Sr)2Si5N8:Eu 2+ , α-SiAlON:Eu 2+ , Ba2Si5N8:Eu 2+ , Ce-activated CALSON phosphors, etc.

[0063] It is also possible to mix a plurality of inorganic phosphors according to the wavelength range of the excitation light or the emission light. For example, when irradiating with ultraviolet excitation light to obtain white light, inorganic phosphors having emission peaks in blue, green, yellow, and red may be mixed and used. When irradiating with blue excitation light to obtain yellow to red light, inorganic phosphors having emission peaks in yellow and red may be mixed and used.

[0064] For example, in the light-emitting device 3, when yellow shift is suppressed and a redder chromaticity is designed, a CASN phosphor or an SCASN phosphor (a phosphor in which part of the Ca in a CASN phosphor is replaced with Sr) can be selected.

[0065] Furthermore, when selecting a CASN or SCASN phosphor, it is desirable to use it in combination with another phosphor having a yellow-red, so-called amber emission peak, such as α-SiAlON. In this case, the ratio of the content of the CASN and / or SCASN phosphor to the content of all phosphors is, in mass %, preferably 0.1% to 30%, more preferably 1% to 25%, and even more preferably 3% to 20%. This makes it easier to achieve a redder chromaticity in the light-emitting device 3, making it easier to emit light of the desired chromaticity when irradiated with light from an LED or LD.

[0066] Furthermore, when a mixture of α-SiAlON, CASN phosphor, and / or SCASN phosphor is used as the phosphor powder, the value of (CASN phosphor + SCASN phosphor) / α-SiAlON is preferably 0 or more in mass ratio, more preferably 0.01 or more, even more preferably 0.02 or more, even more preferably 0.03 or more, and even more preferably 0.05 or more. Furthermore, the value of (CASN phosphor + SCASN phosphor) / α-SiAlON is preferably 1 or less in mass ratio, more preferably 0.5 or less, and more preferably 0.3 or less. Note that (CASN phosphor + SCASN phosphor) refers to the total amount of CASN phosphor and SCASN phosphor contained.

[0067] CASN phosphors and SCASN phosphors have the problem that they are difficult to encapsulate efficiently (without degradation), for example. Therefore, if the ratio (CASN phosphor + SCASN phosphor) / α-SiAlON is too large and an inorganic matrix 11 with a high softening point is used in the wavelength conversion member 1, the phosphor may deteriorate during the firing process during manufacturing, resulting in a decrease in the luminescence intensity of the wavelength conversion member 1. Therefore, when selecting a CASN phosphor or SCASN phosphor, it is desirable to use, for example, a low-softening-point glass as the inorganic matrix 11.

[0068] Examples of low-softening point glasses that can be used include phosphate-based glasses, tin-phosphate-based glasses, bismuthate-based glasses, and tellurite-based glasses. Furthermore, as the borosilicate glass, glass containing, in mole percent, 30% to 80% SiO2, 1% to 40% B2O3, 0.1% to 35% Li2O+Na2O+K2O, 0.1% to 45% MgO+CaO+SrO+BaO, and 0.001% to 10% CeO2+As2O3+MoO2+WO3, or glass containing 30% to 80% SiO2, 1% to 55% B2O3, 0% to 20% Li2O, 0% to 25% Na2O, 0% to 25% K2O, 0.1% to 35% Li2O+Na2O+K2O, and 0.001% to 10% CeO2+As2O3+MoO2+WO3 can also be used.

[0069] In the light-emitting device 3, the yellow shift can be suppressed and a redder chromaticity can be achieved by increasing the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10. However, increasing the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10 may reduce the luminous flux value of the light-emitting device 3. In contrast, for example, as described above, if the inorganic phosphor 12 is designed to contain a CASN phosphor or an SCASN phosphor, the yellow shift can be suppressed and a redder chromaticity can be achieved in the light-emitting device 3. Therefore, the concentration of the inorganic phosphor 12 contained in the wavelength conversion material body 10 can be designed to be low, thereby further increasing the luminous flux value of the light-emitting device 3.

[0070] When a glass matrix is ​​used as the inorganic matrix 11, the inorganic phosphor 12 generally has a higher refractive index than glass. In the wavelength conversion member 1, if the difference in refractive index between the inorganic phosphor 12 and the glass matrix is ​​large, excitation light is more likely to be scattered at the interface between the inorganic phosphor 12 and the glass matrix. As a result, the efficiency of irradiation of the excitation light onto the inorganic phosphor 12 increases, and the luminous efficiency is likely to improve. However, if the difference in refractive index between the inorganic phosphor 12 and the glass matrix is ​​too large, the excitation light is excessively scattered, resulting in scattering loss and, conversely, a decrease in luminous efficiency. In view of the above, the difference in refractive index between the inorganic phosphor 12 and the glass matrix is ​​preferably approximately 0.001 to 0.6. Furthermore, the refractive index (nd) of the glass matrix is ​​preferably 1.45 to 1.8, more preferably 1.47 to 1.75, and even more preferably 1.48 to 1.7.

[0071] The luminous efficiency (lm / W) of the wavelength conversion member 1 varies depending on the type and content of the inorganic phosphor 12, as well as the thickness of the wavelength conversion member 1. The content of the inorganic phosphor 12 and the thickness of the wavelength conversion member 1 can be adjusted appropriately to optimize the luminous efficiency. To obtain the same luminous intensity, increasing the content of the inorganic phosphor 12 allows the thickness of the wavelength conversion member main body 10 to be thinner, which is advantageous for reducing the weight and cost of the light-emitting device 3. If the content of the inorganic phosphor 12 is too low, it becomes difficult to obtain the desired luminous intensity. On the other hand, if the content of the inorganic phosphor 12 is too high, problems such as difficulty in sintering or increased porosity may occur, making it difficult for excitation light to be efficiently irradiated onto the inorganic phosphor 12, or a decrease in the mechanical strength of the wavelength conversion member 1 may occur. From this viewpoint, the content of inorganic phosphor 12 in wavelength conversion member 1 of the present invention is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, even more preferably 20% by mass or more, even more preferably 25% by mass or more, even more preferably 30% by mass or more, preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and particularly preferably 40% by mass or less.

[0072] Average particle diameter D of inorganic phosphor 12 50 is preferably 1 μm or more, 5 μm or more, particularly 10 μm or more, and is preferably 70 μm or less, 50 μm or less, 30 μm or less, or 20 μm or less. If the average particle diameter D50 of the inorganic phosphor 12 is too large, voids are likely to increase when the content of the inorganic phosphor 12 is high. Furthermore, if the content of the inorganic phosphor 12 is low, the inorganic phosphor 12 is likely to become uneven in the wavelength conversion member 1, making it difficult to obtain uniform chromaticity. Furthermore, if the average particle diameter D50 of the inorganic phosphor 12 is too small, the inorganic phosphor 12 will react with the inorganic matrix 11 or foam during firing, increasing the porosity (proportion of remaining bubbles) in the wavelength conversion member 1 and making it more likely that the luminous efficiency will decrease.

[0073] In addition to the inorganic phosphor 12, the wavelength conversion member 1 of the present invention may contain a light diffusing material such as alumina, silica, magnesia, etc. in a total amount of up to 30 mass %.

[0074] The wavelength conversion member 1 of the present invention is preferably made of a powder sintered body. Specifically, it is preferably made of a sintered body of a mixed powder containing an inorganic matrix 11 and an inorganic phosphor powder. In this way, it becomes possible to easily produce a wavelength conversion member 1 in which the inorganic phosphor 12 is uniformly dispersed in the inorganic matrix 11.

[0075] The wavelength conversion member 1 of the present invention can be produced using a slurry containing inorganic particles that form the inorganic matrix 11, inorganic phosphor particles, and organic components such as a binder resin and a solvent. For example, the wavelength conversion member 1 can be formed by applying the slurry to a resin film such as polyethylene terephthalate by a doctor blade method or the like, heating and drying the film to produce a green sheet, and then firing the green sheet. Alternatively, the wavelength conversion member 1 can be formed by applying the slurry to a substrate to form a film, and then drying and firing the resulting film. The wavelength conversion member 1 can also be produced by firing a compact of a mixed powder containing inorganic particles and inorganic phosphor particles.

[0076] When glass powder is used as inorganic particles, the maximum particle diameter of the glass powder is D max The average particle size D50 of the glass powder is preferably 0.1 μm or more, 1 μm or more, and more preferably 2 μm or more, and is preferably 10 μm or less, 8 μm or less, and more preferably 5 μm or less. max If the average particle diameter D of the glass powder is too large, the excitation light is less likely to be scattered in the wavelength conversion member 1 obtained, and the luminous efficiency is likely to decrease. 50 If is too small, the excitation light is scattered excessively in the obtained wavelength conversion member 1, and the luminous efficiency is likely to decrease.

[0077] In the present invention, the maximum particle diameter Dmax and average particle size D 50 indicates a value measured by a laser diffraction method.

[0078] The firing temperature of the mixed powder containing glass powder and inorganic phosphor is preferably equal to or higher than the softening point of the glass powder, preferably higher than the softening point of the glass powder, and more preferably at least 30°C above the softening point of the glass powder. Furthermore, the firing temperature is preferably equal to or lower than the softening point of the glass powder +150°C, more preferably equal to or lower than the softening point of the glass powder +100°C, more preferably equal to or lower than the softening point of the glass powder +90°C, equal to or lower than the softening point of the glass powder +80°C, equal to or lower than the softening point of the glass powder +70°C, equal to or lower than the softening point of the glass powder +60°C, equal to or lower than the softening point of the glass powder +50°C, equal to or lower than the softening point of the glass powder +40°C, equal to or lower than the softening point of the glass powder +30°C, or equal to or lower than the softening point of the glass powder +20°C, more preferably equal to or lower than the softening point of the glass powder +10°C, and even more preferably equal to or lower than the softening point of the glass powder +5°C. If the firing temperature is too low, the glass powder will not flow sufficiently, making it difficult to obtain a dense sintered body. On the other hand, if the firing temperature is too high, the nitride phosphor or oxynitride phosphor may be thermally deteriorated, or the inorganic phosphor may react with the glass, causing foaming and reducing the luminescence intensity and mechanical strength. Furthermore, the inorganic phosphor components may be eluted into the glass, reducing the luminescence intensity, or the inorganic phosphor components may diffuse into the glass, causing the glass to become discolored and reducing the luminescence intensity.

[0079] The firing is preferably carried out in a reduced pressure atmosphere. 5 The pressure is preferably less than 1000 Pa, 1000 Pa or less, and particularly preferably 400 Pa or less. This reduces the amount of bubbles remaining in the wavelength conversion member 1. As a result, the scattering factor in the wavelength conversion member 1 can be reduced, and the luminous efficiency can be improved. The firing may be performed in a vacuum atmosphere, an air atmosphere, or a nitrogen atmosphere. The entire firing process may be performed in a reduced pressure atmosphere, or, for example, only the firing process may be performed in a reduced pressure atmosphere, with the temperature increasing and decreasing processes before and after the firing process being performed in an atmosphere other than a reduced pressure atmosphere (for example, atmospheric pressure).

[0080] The thickness of the wavelength conversion member body 10 is preferably 1000 μm or less, more preferably 800 μm or less, even more preferably 500 μm or less, and particularly preferably 200 μm or less. If the thickness is too large, it becomes difficult to obtain light of the desired color. Furthermore, the luminous efficiency tends to decrease. The thickness of the wavelength conversion member body 10 is preferably 10 μm or more, more preferably 20 μm or more, and particularly preferably 50 μm or more. If the thickness is too small, the mechanical strength of the wavelength conversion member body 10 tends to decrease.

[0081] The surface roughness Ra of at least one surface of the wavelength conversion member body 10 is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. Furthermore, the surface roughness Ra is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. If the surface roughness Ra is too small, the manufacturing cost increases. On the other hand, if the surface roughness Ra is too large, it becomes difficult to form the filter layer 20 uniformly. To adjust the surface roughness, the wavelength conversion member body 10 after firing may be polished using an appropriate polishing pad or polishing grains, but roughening may also be achieved by sandblasting, etching, or the like.

[0082] Furthermore, from the viewpoint of production costs, if the surface roughness Ra of the surface on the emission surface side of the wavelength conversion member main body 10 is regulated, various surface roughnesses Ra can be adopted for the surface on the opposite side to the emission surface (incident surface side) of the wavelength conversion member 1. In this case, the surface roughness Ra of the surface on the opposite side to the emission surface (incident surface side) of the wavelength conversion member 1 may be 2000 nm or less, 1000 nm or less, 500 nm or less, 300 nm or less, or 1 nm or more, 5 nm or more, 10 nm or more, 30 nm or more. In this way, production costs can be easily reduced.

[0083] The shape of the wavelength conversion member 1 of the present invention is not particularly limited, and includes not only members having specific shapes themselves such as plate-like, columnar, hemispherical, and hemispherical dome-like, but also sintered bodies in the form of coatings formed on the surfaces of substrates such as glass substrates and ceramic substrates.

[0084] Next, a second embodiment of the present invention will be described. In the second embodiment, instead of providing the filter layer 20 of the first embodiment, the content of the inorganic phosphor in the wavelength conversion member 100 is strictly defined, thereby suppressing transmission of light in the excitation band of the inorganic phosphor and transmitting light of the emission wavelength of the inorganic phosphor, thereby obtaining light of a desired chromaticity.

[0085] (Second embodiment) 4 is a schematic cross-sectional view showing a wavelength conversion member 100 according to a second embodiment of the present invention. In this embodiment, the wavelength conversion member 100 is formed by dispersing an inorganic phosphor 120 in an inorganic matrix 110. A glass matrix is ​​used as the inorganic matrix 110. The wavelength conversion member 100 does not include a filter layer.

[0086] In the second embodiment of the present invention, the content of the inorganic phosphor 120 in the wavelength conversion member 100 The content is 25% by mass or more.

[0087] The luminous efficiency (lm / W) of the wavelength conversion member 100 varies depending on the type and content of the inorganic phosphor 120, as well as the thickness of the wavelength conversion member 100. The content of the inorganic phosphor 120 and the thickness of the wavelength conversion member 100 can be appropriately adjusted to optimize the luminous efficiency. For the same luminous intensity, increasing the content of the inorganic phosphor 120 allows the thickness of the wavelength conversion member 100 to be thinner, which is advantageous for reducing the weight and cost of the light-emitting device. If the content of the inorganic phosphor 120 is too low, it becomes difficult to suppress the transmission of light at the excitation wavelength of the inorganic phosphor 120, making it difficult to obtain light of the desired chromaticity. It also becomes difficult to obtain the desired luminous intensity. Therefore, the content of the inorganic phosphor 120 in the wavelength conversion member 100 of the present invention is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, even more preferably 45% by mass or more, and even more preferably 50% by mass or more. Furthermore, although there is no upper limit to the content of inorganic phosphor 120, it may become difficult to sinter it or the porosity may increase, making it difficult for excitation light to be efficiently irradiated onto inorganic phosphor 120. Therefore, in reality, the content is preferably 80 mass % or less, more preferably 75 mass % or less, even more preferably 70 mass % or less, even more preferably 65 mass % or less, and even more preferably 60 mass % or less.

[0088] In the second embodiment of the present invention, the same configuration as in the first embodiment can be adopted, except that no filter layer is provided in the wavelength conversion member 100 and the content of inorganic phosphor 120 is higher than in the first embodiment.

[0089] In the first and second embodiments of the present invention, a wavelength conversion member is placed under a light source with an excitation peak wavelength of 450 nm, and light emitted from the underside of the wavelength conversion member is captured in an integrating sphere. The chromaticity calculated from the measured light energy distribution spectrum is preferably chromaticity Cx 0.45 to 0.65 and chromaticity Cy 0.35 to 0.50, more preferably chromaticity Cx 0.49 to 0.65 and chromaticity Cy 0.38 to 0.50, and even more preferably chromaticity Cx 0.50 to 0.60 and chromaticity Cy 0.40 to 0.45. This facilitates the production of a wavelength conversion member with an amber color, which is yellow to red. Furthermore, chromaticity Cz is preferably 0 to 0.15, more preferably 0 to 0.10, and even more preferably 0 to 0.05. In this case, transmission of light in the excitation band of the inorganic phosphor can be more effectively suppressed, making the wavelength conversion member more suitable for use as a component of automotive lighting such as a turn signal lamp.

[0090] The chromaticity of the emitted light from the light-emitting device of the present invention is preferably chromaticity Cx 0.45 to 0.65 and chromaticity Cy 0.35 to 0.50, more preferably chromaticity Cx 0.49 to 0.65 and chromaticity Cy 0.38 to 0.50, and even more preferably chromaticity Cx 0.50 to 0.60 and chromaticity Cy 0.40 to 0.45. This facilitates the production of a light-emitting device with an amber color, which is yellow to red. Furthermore, the chromaticity Cz is preferably 0 to 0.15, more preferably 0 to 0.1, and even more preferably 0 to 0.05. In this case, transmission of light in the excitation band of the inorganic phosphor can be more effectively suppressed. In the first and second embodiments, the chromaticity of the emitted light from the light-emitting device can be calculated from the energy distribution spectrum of light measured by placing a wavelength conversion member directly above a light source with an excitation peak wavelength of 450 nm inside an integrating sphere and capturing the total luminous flux when the light is turned on. [Example]

[0091] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0092] Examples 1 to 6 Glass powder (softening point: 850°C, thermal expansion coefficient: 68.0 × 10) with a composition of SiO2 50%, Al2O 36%, BO 35%, CaO 12%, BaO 25%, and ZnO 2% by mass was used. -7 To the powder (temperature: 1000 K / °C, average particle size: 2.5 μm), α-SiAlON was added in the proportions shown in Table 1 to obtain a mixed powder. α-SiAlON is a phosphor that emits yellow to red, so-called amber fluorescence, with an excitation wavelength of 250 nm to 500 nm and an emission peak wavelength of 600 nm.

[0093] [Table 1]

[0094] The obtained mixed powder was pressure-molded in a mold to produce a preform with a diameter of 20 mm and a thickness of 3 mm. The preform was fired at 850°C to produce a base material. The base material was cut into a plate-shaped base material measuring 12 mm x 12 mm x 0.3 mm, and the plate-shaped base material was lapped and polished using a double-sided polisher to obtain a wavelength conversion member main body with a thickness of 150 μm.

[0095] A wavelength conversion member was obtained by forming a dielectric multilayer film (filter layer) by sputtering on one main surface of the obtained wavelength conversion member body, which was composed of a total of 20 alternating TiO2 layers and SiO2 layers. Figure 5 shows a graph representing the spectral transmittance curve at an incident angle of 0° when the same dielectric multilayer films (filter layers) as those formed in Examples 1 to 6 were deposited on a 0.5 mm thick glass substrate. Table 2 also shows the structure of the dielectric multilayer film. This shows that the transmission of light at the excitation wavelength of the inorganic phosphor was suppressed. It also shows that light at the emission wavelength of the inorganic phosphor was more transmitted.

[0096] [Table 2]

[0097] (Examples 7 and 8 and Comparative Examples 1 to 3) Wavelength conversion members were obtained in the same manner as in Examples 1 to 6, except that mixed powders were obtained in the proportions shown in Tables 1 and 3, and that no dielectric multilayer film was formed, and the wavelength conversion member body was used alone as the wavelength conversion member.

[0098] [Table 3]

[0099] Next, each wavelength conversion element was placed under a light source with an excitation peak wavelength of 450 nm. The light emitted from the bottom of the wavelength conversion element was taken into the integrating sphere and then guided into a spectrometer (Ocean Photonics, USB2000) that had been wavelength-calibrated using a standard light source, and the light energy distribution spectrum was measured. Here, the LED and wavelength conversion element were spaced 5 mm apart, and the wavelength conversion element was placed so that it covered the φ2 mm hole at the top of the integrating sphere. The wavelength conversion element was also placed so that the dielectric multilayer film was on the side (exit surface) opposite the light source with an excitation peak wavelength of 450 nm. The results are shown in Figures 6 to 8.

[0100] As shown in Figures 6 to 8, in Examples 1 to 6 in which a dielectric multilayer film was formed, it was found that the transmission of light at the excitation wavelength of the inorganic phosphor was effectively suppressed and light at the emission wavelength of the inorganic phosphor was more transmitted. On the other hand, it was found that in Comparative Examples 1 to 3, the transmission of light at the excitation wavelength of the inorganic phosphor, which is blue light, was not sufficiently suppressed. Furthermore, in Figure 6, it was found that the excitation light reflected by the dielectric multilayer film returned to the inside of the wavelength conversion member, making it easier to excite the phosphor particles, resulting in increased fluorescence intensity. Furthermore, it was found that in Examples 7 and 8, the wavelength conversion member contained a large amount of inorganic phosphor, at 30 mass% or more, and thus the transmission of light at the excitation wavelength of the inorganic phosphor was effectively suppressed.

[0101] (Calculation of chromaticity Cx, Cy, Cz) Next, the chromaticities Cx, Cy, and Cz of the wavelength conversion member were calculated from the light energy distribution spectrum obtained earlier. The chromaticities Cx, Cy, and Cz were determined by integrating the spectrum using the CIE 1931 2-deg, x(_), y(_), z(_) color matching functions to find the tristimulus values ​​XYZ. From these tristimulus values ​​XYZ, the chromaticity Cx = X / (X+Y+Z), chromaticity Cy = Y / (X+Y+Z), and chromaticity Cz = Z / (X+Y+Z) were calculated. The results are shown in Figure 9, Tables 1 and 3.

[0102] 9, it was found that the chromaticity Cx and Cy of Examples 1 to 8 were within the range of amber color indexes, chromaticity Cx 0.45 to 0.65 and chromaticity Cy 0.35 to 0.50. On the other hand, it was found that in Comparative Examples 1 to 3, the transmission of the excitation wavelength light was not sufficiently suppressed, and therefore the excitation wavelength light and the emission wavelength light were combined, resulting in a whitish color.

[0103] (Luminous flux value) The luminous flux value of the obtained wavelength conversion member was calculated by multiplying the above-mentioned light energy distribution spectrum by the standard relative luminous efficiency, integrating the result over wavelengths of 380 to 780 nm, and multiplying it by a conversion coefficient of 683. Thereafter, the relative luminous flux value of each sample was determined when the luminous flux value of Example 1 was set to 1.00. The results are shown in Tables 1 and 3 above.

[0104] Example 9 A wavelength conversion member was obtained in the same manner as in Example 1, except that the thickness of the wavelength conversion member body was 120 μm, the content of the inorganic phosphor was 25 mass %, and the dielectric multilayer film was configured as shown in Table 4 below (total number of layers in the dielectric multilayer film: 26).

[0105] [Table 4]

[0106] Example 10 A wavelength conversion member was obtained in the same manner as in Example 1, except that the thickness of the wavelength conversion member body was 120 μm, the content of the inorganic phosphor was 25 mass %, and the dielectric multilayer film was configured as shown in Table 5 below (total number of layers in the dielectric multilayer film: 26).

[0107] [Table 5]

[0108] Example 11 A wavelength conversion member was obtained in the same manner as in Example 1, except that the thickness of the wavelength conversion member body was 120 μm, the content of the inorganic phosphor was 25 mass %, and the dielectric multilayer film was configured as shown in Table 6 below (total number of layers in the dielectric multilayer film: 26).

[0109] [Table 6]

[0110] Fig. 10 is a graph showing the spectral transmittance curve at an incident angle of 0° when the same dielectric multilayer film (filter layer) as used in Examples 9 to 11 is formed on a glass substrate with a thickness of 0.5 mm. For reference, Fig. 10 also shows the blue LED spectrum.

[0111] As shown in FIG. 10, the cut-on wavelength of the filter layer of Example 9 was 510 nm, the cut-on wavelength of the filter layer of Example 10 was 547 nm, and the cut-on wavelength of the filter layer of Example 11 was 567 nm.

[0112] Next, the light energy distribution spectrum (emission spectrum) of the wavelength conversion members obtained in Examples 9 to 11 was measured in the same manner as in Examples 1 to 8 and Comparative Examples 1 to 3. The results are shown in FIG.

[0113] 11, it can be seen that the filter layers of Examples 9 to 11 effectively suppress the transmission of light in the excitation band of the inorganic phosphor and transmit light of the emission wavelength of the inorganic phosphor. It can also be seen that the larger the cut-on wavelength of the filter layer, the more effectively the filter layer can suppress the transmission of light in the excitation band of the inorganic phosphor.

[0114] Example 12 A wavelength conversion member was obtained in the same manner as in Example 10, except that a mixture of α-SiAlON and SCASN (α-SiAlON:SCASN=90:10 in mass ratio) was added as the phosphor powder so that the total content of inorganic phosphors was 25 mass %. SCASN is a phosphor that emits red fluorescence, with an excitation band wavelength of 300 nm to 500 nm and an emission peak wavelength of 630 nm.

[0115] Example 13 A wavelength conversion member was obtained in the same manner as in Example 12, except that the glass powder was a glass powder (softening point: 695°C, average particle size: 2.5 μm) having a composition, in mass %, of SiO2 63%, Al2O 36%, BO 38%, Li2O 2%, Na2O 5%, KO 4%, BaO 7%, ZnO 4%, and CeO 21%, and a mixture of α-SiAlON and SCASN (mass ratio of α-SiAlON:SCASN = 90:10) was added as the phosphor powder so that the total content of inorganic phosphors was 17 mass %.

[0116] Next, the chromaticity Cx, Cy, Cz and luminous flux values ​​of the wavelength conversion members obtained in Examples 9 to 13 were measured in the same manner as in Examples 1 to 8 and Comparative Examples 1 to 3. The results are shown in Table 7 below. The luminous flux values ​​of the obtained wavelength conversion members were calculated by multiplying the above-mentioned light energy distribution spectrum by the standard relative luminous efficiency, and then the relative luminous flux value of each sample was determined when the luminous flux value of Example 10 was set to 1.00.

[0117] [Table 7] [Industrial Applicability]

[0118] The wavelength conversion member of the present invention is suitable as a component for general lighting such as white LEDs and special lighting (for example, projector light sources, vehicle lighting such as vehicle headlights and turn signals). [Explanation of symbols]

[0119] 1, 100 Wavelength conversion material 10 Wavelength conversion member body 11, 110 Inorganic matrix 12, 120 Inorganic phosphors 20 filter layers 3 Light-emitting devices 30 light source 40 Dielectric multilayer film 41L low refractive index layer 41H high refractive index layer L0 Excitation wavelength light (excitation light) L1 Emission wavelength light (fluorescence)

Claims

1. A wavelength conversion member comprising a wavelength conversion member body formed by dispersing an inorganic phosphor in an inorganic matrix, and a filter layer provided on one surface of the wavelength conversion member body, The filter layer suppresses transmission of light in an excitation band of the inorganic phosphor; A wavelength conversion member that transmits light having an emission peak wavelength of the inorganic phosphor.

2. 2. The wavelength conversion member according to claim 1, wherein the excitation band of the inorganic phosphor is between 300 nm and 480 nm in wavelength, and the emission peak wavelength of the inorganic phosphor is 500 nm or more and 700 nm or less.

3. 3. The wavelength conversion member according to claim 1, wherein the filter layer is a dielectric multilayer film.

4. 4. The wavelength conversion member according to claim 3, wherein the total number of layers of the dielectric multilayer film is 10 or more.

5. 3. The wavelength conversion member according to claim 1, wherein the inorganic phosphor comprises at least one selected from the group consisting of a nitride phosphor and an oxynitride phosphor.

6. 3. The wavelength conversion member according to claim 1, wherein the inorganic matrix contains glass or ceramics.

7. The wavelength conversion member according to claim 1 or 2, characterized in that the wavelength conversion member is placed under a light source having an excitation peak wavelength of 450 nm, and the chromaticity calculated from the energy distribution spectrum of light measured by taking light emitted from a lower surface of the wavelength conversion member into an integrating sphere is a chromaticity Cx of 0.45 to 0.65 and a chromaticity Cy of 0.35 to 0.

50.

8. 3. The wavelength conversion member according to claim 1, wherein the cut-on wavelength of the filter layer is 480 nm or more and 680 nm or less.

9. 3. The wavelength conversion member according to claim 1, wherein the filter layer is disposed on the emission surface side of the wavelength conversion member.

10. 10. The wavelength conversion member according to claim 9, wherein the filter layer also serves as a filter for cutting a part of the emission spectrum of the inorganic phosphor on the short wavelength side.

11. A wavelength conversion member having an inorganic phosphor dispersed in an inorganic matrix, the inorganic phosphor includes at least one selected from the group consisting of an oxide phosphor, a nitride phosphor, an oxynitride phosphor, a chloride phosphor, an oxychloride phosphor, a halide phosphor, an aluminate phosphor, and a halophosphate chloride phosphor; A wavelength conversion member, comprising the inorganic phosphor having a content of 25 mass % or more.

Citation Information

Patent Citations

  • JP1973095541A

  • Light-emitting diode

    JP2000208815A

  • Emission color converting member

    JP2003258308A